"Lupòroom": per una drammaturgia delle mutande: Intervista a Paolo Gubello - Di Vita, Vincenza (Mimesis Journal, 2015)
Paul Gubello describes his approach to writing and performing for the production of the Lupòroom, loosely based on the popular fairy tale Little Red Riding Hood. Gubello stresses the how he has chosen the perspective of the bad wolf, interpreted as the contemporary appearance of a serial perverted portrait through stereotypes.